1987
DOI: 10.3989/collectbot.1988.v17.159
|View full text |Cite
|
Sign up to set email alerts
|

Notas sobre taxonomía y nomenclatura de plantas, III

Abstract: Notas nomenclaturales y taxonómicas referentes a plantas de la "Flora dels Països Catalans" en preparación. Este texto es continuación de los que han aparecido en el Butll. Inst. Catalana Hist. Nat. 38: 63-89 (1984) y en Collect. Bot. (Barcelona) 11: 25-89 (1979) y 14: 89-103 (1983).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…Four infraspecific taxa were reported from France (Kerguélen, 1999), and some related species were also described by Jordan & Fourreau (1868;e.g., A. brigantiacum, A. orophilum and A. rhodanense), but were later treated as synonyms of A. montanum (Kerguélen, 1993(Kerguélen, , 1999. Several infraspecific taxa of A. montanum were also described from Spain (e.g., Bolòs & Vigo, 1974); later, all of them were considered synonyms of A. montanum (Küpfer & Nieto Feliner, 1993, with updates at http://www.floraiberica .es/). A number of varieties have also been reported from northern Africa (Maire, 1967).…”
Section: Taxonomy and Evolutionary History Of Alyssum Montanum (Brassmentioning
confidence: 99%
“…Four infraspecific taxa were reported from France (Kerguélen, 1999), and some related species were also described by Jordan & Fourreau (1868;e.g., A. brigantiacum, A. orophilum and A. rhodanense), but were later treated as synonyms of A. montanum (Kerguélen, 1993(Kerguélen, , 1999. Several infraspecific taxa of A. montanum were also described from Spain (e.g., Bolòs & Vigo, 1974); later, all of them were considered synonyms of A. montanum (Küpfer & Nieto Feliner, 1993, with updates at http://www.floraiberica .es/). A number of varieties have also been reported from northern Africa (Maire, 1967).…”
Section: Taxonomy and Evolutionary History Of Alyssum Montanum (Brassmentioning
confidence: 99%
“…2013, integrating the field observations. This was useful to define vegetation series, interpreting the spatial distribution and surfaces of studied communities according to De Bolòs (1963), Géhu (1991), Biondi (1996), andRivas-Martinez (1994). This helped us to better define syndynamics (i.e., succession, transgression, regression, fluctuation, regeneration, degeneration) and to relatively adjust the human pressure related values during the assessment (according to Faliński, 1999;Falińska, 2003;Pedrotti, 2013).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Coronilla montserratii is a taxonomic synonym of C. repanda var. montserratii O. Bolòs & Vigo (Bolòs & Vigo 1974). Remarks: This variety has been included within G. communis L. without any taxonomic distinction (Alonso & Crespo, 2013 Bräuchler et al (2008) selected the same lectotype chosen by the early work of Rosselló & Sáez (2001: 102).…”
Section: Hieracium Balearicummentioning
confidence: 99%
“…alaternus and the Balearic endemic R. ludovici-salvatoris Chodat. Previously, the name R. ×jacobisalvadori O. Bolòs & Vigo was believed to apply to the hybrid between both species (Bolòs & Vigo, 1974). However, the study of Rosselló & Mus (1988) clearly revealed that the holotype could not be distinguished from R. alaternus, and it was considered as a mere variation of this species.…”
Section: Rhamnaceaementioning
confidence: 99%